LINC02139 interacts with and stabilizes XIAP to regulate cell proliferation and apoptosis in gastric cancer - Miaomiao Pei; Jieming Zhang; Zhen Yu; Ying Peng; Yidong Chen; Siyang Peng; Xiangyang Wei; Jieke Wu; Xiaodong Huang; Yanci Xie; Ping Yang; Linjie Hong; et al. (Communications Biology)
Abstract Previous reports showed that long non-coding RNA (lncRNA) participates in the development and progression of tumors. Nevertheless, the effect of LINC02139 and its mechanism on gastric cancer (GC) is still unknown. We revealed that LINC02139 is upregulated in GC cell lines and tissues and high LINC02139 expression was correlated with the advancement of GC in patients. Functionally, overexpression of LINC02139 promoted, while knockdown of LINC02139 impaired GC cell proliferation, migration, and invasion in vitro and impeded tumorigenesis in a tumor xenograft model in vivo. Mechanistically, LINC02139 directly bound to XIAP and increased the protein level by maintaining its protein stability through inhibition of the ubiquitination and proteasome-dependent degradation pathway. Importantly, the regulatory function of XIAP in LINC02139-mediated oncogenic effects was demonstrated. Both in vitro and in vivo experiments showed that LINC02139 and XIAP collaboratively modulate GC cell growth and apoptosis. Analysis of clinical GC tissues further confirmed the upregulation of XIAP and the positive association between LINC02139 and XIAP expression. These findings established LINC02139 as a driver of tumorigenesis and highlighted the crucial involvement of the LINC02139-XIAP axis in GC progression, suggesting its potential as a promising therapeutic target for combating GC advancement.